Suplementação da dieta de frangos com calcários extraídos de jazidas da região semiárida do nordeste brasileiro - Albuquerque, Lucas Notaro de (2017)
The aim was to estimate the requirements and biological availability of calcium of limestones extracted from Brazilian Northeast deposits. A total of 975 male broilers (Cobb-500® strain) weighed at eight days of age, 193 ± 0.44 g, and distributed in completely randomized design in 4 x 3 + 1 factorial arrangement (4 limestone sources x 3 calcium levels + 1 basal calcium level), resulting in 13 treatments with five replications of 15 birds. Commercial samples of the following limestones were studied: A. Calcium carbonate (metamorphic origin) with 38.9% Ca+2, theoretically the standard source with 100% of calcium available; B. Calcitic limestone of sedimentary origin (IMAP®) with 41.82% Ca+2; C. Calcitic limestone of metamorphic origin (sample 1) with 34.00% de Ca+2, and, D. Calcitic limestone of metamorphic origin (sample 2) with 35.90% de Ca+2 that replaced kaolin from basal diet for provide increased calcium levels (0.40, 0.62, 0.84 and 1.06%). The in vitro solubilities were determined in 0.2 N HCl. The performance and bone resistance of tibia were evaluated. Calcium requirements were estimated by polynomial regression and availability by slope ratio tecnique. The source means were evaluated by tukey test (P ≤ 0.05). The WG and bone resistance of tibia were highest (P ≤ 0.05) in broilers receiving diet with limestone B, however, the FCR was not changed (P ˃ 0.05) The B limestone improved the FC in compare with the A and D limestones (P ≤ 0.05). The limestone average solubilities were 90.02, 56.31, 48.38 e 48.11%, while the calcium average requirements were 0.88, 0.75, 0.82 e 0.97%, and average availabilities were 100, 121, 83 e 74%, respectively for A, B, C and D limestones sources. The calcium bioavailability and requirement for broilers of 8 to 21 days of age are affected by the limestone origin. The B limestone calcium, of sedimentary origin, is more available and their inclusion in the initial diet requires less limestone and calcium to attend the broilers requirements than the inclusions of limestone A, C and D of metamorphic origins.